Interpretation and diplomacy aspects of authority and care in imaging reports - Golder, Werner (World Journal of Nuclear Medicine, 2017)
Whereas the creative performance of the physician for nuclear medicine is measured against his/her written report, the value of the message will not only be judged by the precision of the medical statement. The same result can be attributed to different words. Numerous habitual and accidental factors exert influence on the decision on what is said and what is not said, how it is assessed, and what is ignored. The less certain a diagnosis is, and the less favorable its possible consequences are, the more subtleties and paraphrases should be expected within the report. The decision on the nature and the volume of the written report will not only be taken by the time of recording, but the way is prepared by the knowledge of the patient's history and symptoms, the personal relationship to him/her as well as by a set of conditions throughout the inspection of the images. The intuitiveness accompanying the information transfer in imaging diagnostics does not only explain the differences in volume and depth of diagnosis and differential diagnosis but also the range of diagnostic and therapeutic recommendations.
Keywords: Empathy; imaging report; interpretation; objectivity; recommendation